Anaxarchus of Abdera: Adiaphoria and Criterion of Truth on the Threshold of Hellenistic Age - Pajón Leyra, Ignacio (Revista Archai, 2019)
The philosophical doctrine of Anaxarchus of Abdera is nowadays not very well known. This notwithstanding, Anaxarchus was a character of key importance in the development of Hellenistic philosophy. His ethics, in particular, is one of the first theories in stating that the ultimate goal of life is happiness (the so-called eudaimonism). Moreover, he suggests that the only way to reach that goal is adiaphoria, i.e. ‘indifference’. However, the sceptic interpretation of adiaphoria as denial of the criterion of truth will turn Anaxarchus into a figure not related to sceptic thought, from the point of view of the sceptic philosophers themselves. The purpose of this paper is to analyse the way how Hellenistic and Roman tradition construed the role of Anaxarchus’ eudaimonia and the place of this author in the development of thought in this period.